Current Applications and the Future of Phage Therapy for Periprosthetic Joint Infections - Arian Ocean Abedi; Armita Armina Abedi; Tristan Ferry; Mustafa Citak (Antibiotics, 2025)
Periprosthetic joint infections (PJI) present significant challenges in orthopedic surgery, largely due to the complexity of treating antibiotic-resistant infections. Phage therapy, which utilizes bacteriophages to target bacterial pathogens, offers a promising supplement to traditional antimicrobial methods. This review discusses the current applications of phage therapy in the management of PJI, exploring its underlying mechanisms, clinical outcomes, and practical considerations. We also explore advances in phage therapy technology, including the development of phage cocktails, bioengineered phages, and combination therapies with antibiotics, which enhance the specificity and effectiveness of treatments. Furthermore, we address the future potential of phage therapy to be integrated into standard treatment protocols, focusing on ongoing innovations and research areas.The regulatory and ethical aspects of phage therapy in clinical settings are also discussed. By offering a comprehensive evaluation of both the current state and prospects of phage therapy, this review aims to inform clinical practice and stimulate further research into this innovative treatment modality for PJI management.